Type I and Type III Interferons Display Different Dependency on Mitogen-Activated Protein Kinases to Mount an Antiviral State in the Human Gut - Pervolaraki, Kalliopi; Stanifer, Megan L.; Münchau, Stephanie; Renn, Lynnsey A.; Albrecht, Dorothee; Kurzhals, Stefan; Senís, Elena; Grimm, Dirk; Schröder-Braunstein, Jutta; Rabin, Ronald L.; Boulant, Steeve (Frontiers in Immunology, 2017)
Intestinal epithelial cells (IECs) are constantly exposed to commensal flora and pathogen challenges. How IECs regulate their innate immune response to maintain gut homeostasis remains unclear. Interferons (IFNs) are cytokines produced during infections. While type I IFN receptors are ubiquitously expressed, type III IFN receptors are expressed only on epithelial cells. This epithelium specificity strongly suggests exclusive functions at epithelial surfaces, but the relative roles of type I and III IFNs in the establishment of an antiviral innate immune response in human IECs are not clearly defined. Here, we used mini-gut organoids to define the functions of types I and III IFNs to protect the human gut against viral infection. We show that primary non-transformed human IECs, upon viral challenge, upregulate the expression of both type I and type III IFNs at the transcriptional level but only secrete type III IFN in the supernatant. However, human IECs respond to both type I and type III IFNs by producing IFN stimulated genes (ISGs) that in turn induce an antiviral state. Using genetic ablation of either type I or type III IFN receptors, we show that either IFN can independently restrict virus infection in human IECs. Importantly, we report, for the first-time, differences in the mechanisms by which each IFN establishes the antiviral state. Contrary to type I IFN, the antiviral activity induced by type III IFN is strongly dependent on the mitogen-activated protein kinases (MAPK) signaling pathway, suggesting a pathway used by type III IFNs that non-redundantly contributes to the antiviral state. In conclusion, we demonstrate that hIECs specifically regulate their innate immune response favoring type III IFN-mediated signaling which allows for efficient protection against pathogens without producing excessive inflammation. Our results strongly suggest that type III IFN constitutes the frontline of antiviral response in the human gut. We propose that mucosal surfaces, particularly the gastro-intestinal tract, have evolved to favor type III IFN-mediated response to pathogen infections as it allows for spatial segregation of signaling and moderate production of inflammatory signals which we propose are key to maintain gut homeostasis.